ANALISIS TINGKAT PEMAHAMAN GURU TERHADAP KEGIATAN PEMBELAJARAN PADA TAMAN KANAK-KANAK DI KOTA PONTIANAK - Zamzami, Ury (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The level ofÂ  teacher's comprehension towards learning process is required as the main modal to learning management success. Therefore, the researcher aims to gain awarness deeper about the level of teacher's comprehension towards learning activity at Kindergarten in Pontianak. The method that is used in this research is descriptive. The approach used in this research is quantitative approach and is explicated in descriptive. Whilst the technique of data collection are test and documentation. Technique of dataanalysis that is used in this research is formulation of entral tendency of mean, modes and standar deviation. Based on the result of data analysis, shows that in opening activity of comprehension level in translating to medium category is 60 teachers or 62.50%, the level of teacher's comprehension in estimating is on medium of 74 teachers or 77.08% and the level of teacher's comprehension in forcasting is 57 or 59.38%. During the core activity, the teacher's comprehension level of in translating is medium in 68 teachers or 70.83%, teacher's comprehension level in estimating is medium in 70 teachers or 72.92%, and the level of teacher's comprehension in forcasting is mulled as medium in the point of 70.84%. Whilst during the closing activity, the comprehension level of teacher is medium at 47.92% or 46 teachers, the comprehension level of teacher in estimating is in medium category of 68.75%, and the comprehension level of teacher in forecasting is too in medium category, 67.71%. Keywords: comprehension level, learning activity